Changes in the Concentration of Purine and Pyridine as a Response to Single Whole-Body Cryostimulation - Dudzinska, Wioleta; Lubkowska, Anna (Frontiers in Physiology, 2021)
To our knowledge, this is the first study in which we provide evidence that a single whole-body cryostimulation treatment leads to changes associated with erythrocyte energy metabolism. These changes are beneficial from the point of view of cellular bioenergetics, because they are associated with an increase in ATP concentration and erythrocyte energy potential expressed by an increase in the ATP/ADP and ATP/AMP ratios and the value of adenylate energy charge (AEC). In addition, as affected by cryogenic temperatures, there is a decrease in the concentration of purine catabolism products, i.e., inosine and hypoxanthine in the blood.